Improving biochemical markers for disorders of N-glycosylation - Freeze, Hudson H. (Annals of Translational Medicine, 2019)
Identification of new biomarkers for diseases or improved sensitivity of established ones can help identify patients, track their natural history, and monitor the efficacy of potential therapies. All clearly benefit patients. In a recent paper by Chen et al. (1), the authors apply a highly sensitive, commercialized method to the analysis of a few patients with several different congenital disorders of glycosylation (CDG). The method significantly expands quantitative glycomic information available for patients. These results are encouraging, however, analysis of many more samples will be required to have sufficient confidence in its general usefulness for CDG patients.